Chapter A corpus-based approach to manual simultaneity - Sáfár, Anna (De Gruyter, 2013)
The purpose of this paper is to describe a corpus-based approach to the study of manual simultaneity (in particular manual holds) and our first attempt at implementing it for the Sign Language of the Netherlands (Nederlandse Gebarentaal, NGT). After discussing previous research on the subject and the new insights we expect from a corpus-based analysis, we present our annotation guidelines and evaluate them based on a pilot study on the Corpus NGT.